Effectiveness of a Patient Support Program in Supporting Access to Therapy for Solid Tumor Malignancies - Lindsay Parker; Alissa Shaul; Brian Murphy; Zeba M. Khan (Journal of Health Economics and Outcomes Research)
**Background:** Certain governmental agencies, patient advocacy organizations, and pharmaceutical manufacturers have implemented programs to assist patients in overcoming barriers to accessing healthcare. Recently, such programs have expanded their services, helping both uninsured and insured patients to navigate the complex healthcare system, and assisting with increasing out-of pocket costs and copays for the drugs.